2013
DOI: 10.1186/1746-6148-9-110
|View full text |Cite
|
Sign up to set email alerts
|

Histological and molecular characterisation of feline humeral condylar osteoarthritis

Abstract: BackgroundOsteoarthritis (OA) is a clinically important and common disease of older cats. The pathological changes and molecular mechanisms which underpin the disease have yet to be described. In this study we evaluated selected histological and transcriptomic measures in the articular cartilage and subchondral bone (SCB) of the humeral condyle of cats with or without OA.ResultsThe histomorphometric changes in humeral condyle were concentrated in the medial aspect of the condyle. Cats with OA had a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In other reports, inflammatory and immunemediated etiology has been suggested as the cause of primary DJD in cats (14), and immune dysfunction has been seen in association with DJD in a genomic/proteomic study (15). Some studies have reported the pathology of feline arthritis (16,17), and it is gradually being elucidated. To further our understanding of the pathophysiology of feline DJD, it is necessary to prove these relationships precisely (18).…”
Section: Discussionmentioning
confidence: 97%
“…In other reports, inflammatory and immunemediated etiology has been suggested as the cause of primary DJD in cats (14), and immune dysfunction has been seen in association with DJD in a genomic/proteomic study (15). Some studies have reported the pathology of feline arthritis (16,17), and it is gradually being elucidated. To further our understanding of the pathophysiology of feline DJD, it is necessary to prove these relationships precisely (18).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, cats represent another physiologically well-characterized domesticated animal that has been used in aging studies (149,(154)(155)(156). As in dogs, several pathological age-associated processes occur in felines, including kidney disease, arthritis, sarcopenia, and neurological decline (149,(154)(155)(156). Cats live an average of 12-14 years, and life-span studies in this species are therefore also problematic (157); however, their aging phenotype may make them attractive models.…”
Section: Dogs and Catsmentioning
confidence: 99%
“…3) 30e33 . OA in cats also appears to be very similar to the human condition 34,35 . Estimates of the number of dogs with clinical signs associated with OA are 20% of the population, translating to at least 15 million dogs in the US alone.…”
mentioning
confidence: 57%